Riverwatch dissolved oxygen predicting software using neural network - Disu, Sherwin P. (1998)
A river's state can be designed by its chemical and physical properties. These properties are determined by the amount of dissolved oxygen (DO) in the river. A river that is DO-saturated has 8-9 mg/L DO density. Experts say that is it is pace with the rate at which it is being depleted. While a 1-2 mg/L DO density indicates a higher demand for oxygen signifying a large amount of organic and inorganic deposit in the river contributing to the Biological Oxygen Demand (BOD) and to the Chemical Oxygen Demand (COD) respectively. At this DO level, the river starts dying. Factors affecting the DO level of river such as amount of organic and inorganic materials in the river, flow rate and temperature among others are presently being observed and analyze in the hope of relating them to form a useful equation that will help environmentalists and authorities predict the amount of organic and inorganic deposits a river can tolerate by determining the river's DO level. Unfortunately, the very much needed equation may not possibly be formulated for reason of extreme difficulty in relating the involved factors. Even if an equation surfaces, its preciseness would be doubted and therefore would have to be proven accurate. An alternative approach in addressing the need would be to approximate. Using available data, a neural network could predict the DO level of a river. This is what Riverwatch intends to accomplish. Predicting DO percent saturation of a river would be of great help in knowing the limit of amount of waste a river can tolerate. A knowledge of this will lead to the development of waste management scheme that will help in preventing the extinction of river systems.
Thesis (B.S. Computer Science)--University of the Philippines, Diliman.
Keywords: Water -- Dissolved oxygen -- Data processing; Water quality -- Measurement -- Equipment and supplies; Water -- Dissolved oxygen -- Measurement; Neural networks (Computer Science); Riverwatch